SAT0360 Henoch - Schönlein Purpura in Adults: Data from A Referral Center in Sweden. (15th July 2016) - Marketos, N.; Segelmark, M.
Abstract : Background: Henoch-Schönlein purpura or IgA vasculitis (IgAV) is a systemic vasculitis encountered both in children and adults. It may lead either to single-organ vasculitis as cutaneous IgAV or a systemic disease 1 . IgAV in adults is considered to have worse clinical features and outcome compared to that of children 2 . Objectives: Retrospective analysis of 43 consecutive adult IgAV patients referred to a secondary and tertiary referral centrum in a Swedish university hospital between 2008 and 2014. Methods: Electronic records of patients were reviewed. EULAR/PRINTO/PRES and ACR criteria for diagnosis and EUVAS criteria for disease activity were applied 3 . MedCalc Statistical Software version 15.11.4 (MedCalc Software bvba, Ostend, Belgium) was used. Results: Twenty-eight of the patients were male and 15 female. Mean age at disease onset was 43 (SD=21) years. Ten of 43 patients (23%) suffered an upper respiratory tract infection prior to disease onset. All 4 major organs were involved in 12/43 patients (28%). Skin vasculitis was present in 40 (93%), arthritis in 13 (30%), gastrointestinal involvement in 22 (51%) and renal manifestations in 29 patients (67%). Nine patients (21%) had positive findings from either endoscopy or computed tomography. Twenty of 34 patients examined (59%) had various cellular casts. Seventeen patients (40%) had albuminuria and 29 (67%) hematuria. Skin biopsy showed leucocytoclastic vasculitis in 63% of all 43 patients. IgA was shown in 9/11 renal (82%) and in 27/29 (93%) skin biopsies. Five skin biopsies had IgM deposition whereas 3 had both IgM and IgG. All 8 patients had renal involvement (χ 2 =4, 12, p=0, 04). Regarding treatment, 86% of the patients received prednisolone while 30/43 (70%) were given other immune therapy, namely mycophenolate mofetil in 6/43 (14%). Time to joint remission was shorter for women (p=0.04) but renal remission was shorter for men (p=0.001). Thirty out of 43 patients (70%) had just one incidence of IgAV while 9/43 (21%) had more than one episode, in some cases even 4 or 5 relapses. Conclusions: These results confirm those from other centra 2 in an attempt to elucidate IgAV in adults. Time to remission is to our knowledge not previously studied. Unique in this study was the finding that joint response was statistically significant slower in men than women and the opposite was observed regarding renal response. IgM deposition in skin biopsy was associated to renal involvement. The outcomes may vary depending on period of follow-up and age of patients. In the lack of therapeutic consensus guidelines, treatment continues to be symptomatic and immunomodulation regimens are reserved for those with more severe disease. These results need to be confirmed in larger cohorts. References: Jennette, J. C. et al. 2012 revised International Chapel Hill Consensus Conference Nomenclature of Vasculitides. Arthritis Rheum. 65, 1–11 (2013) Calvo-Río, V. et al. Henoch-Schönlein purpura in northern Spain: clinical spectrum of the disease in 417 patients from a single center. Medicine (Baltimore). 93, 106–13 (2014) Flossmann, O. et al. Development of comprehensive disease assessment in systemic vasculitis. Postgrad. Med. J. 84, 143–152 (2008) Disclosure of Interest: None declared